PENDIDIKAN MULTIKULTURAL DAN MULTIKULTURALISME DI INDONESIA (REALITAS, TANTANGAN, DAN HARAPAN) - Agus Sutono (Bahasa Indonesia, 2018)
Indonesia is a society with a plurality of the most complex among other countries in the region, even with countries in the region as well as other African continent. Plural society is a society that presupposes the existence of pluralistic situation elements or arrangements in social lives side by side, but not fused into a single political unit Multicultural education is a good option for the nursery generation of Indonesian people who actually have passed down over the years. Multicultural Education is no longer just focus on racial groups, religious, and cultural dominant or mainstream, as mentioned above once the pressure on education intercultural emphasize increased understanding and tolerance of individuals coming from minority groups against mainstream dominant culture, which ultimately led to people from minority groups are integrated into mainstream society. Multicultural education is actually an attitude of "care" and want to understand (difference), or the politics of recognition (rang-political recognition of people from minority groups). Moreover, Multicultural Education also includes the notion of consideration of the policies and strategies of education in a multi-cultural society. Therefore Multicultural Education also includes subjects such as tolerance, diversity ethno-cultural and religious, discrimination, conflict resolution, human rights, democracy and plurality, and other relevant subjects.